(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study aims to recognize the level of the influence of the internal environment on the organizational commitment of the staff of Al- Istiqlal University. The internal environment is one of the most important elements of organizational commitment in the work environment. The study also seeks to identify the level of influence of organizational structure and organizational culture on the organizational commitment of the employees of Al- Istiqlal University. This study has many recommendations and provide the university with feedback on the researched topic, which will benefit and enrich the university experience in improving organizational commitment levels. A random sample was selected from the university employees. This sample is (183) of the study population (347), In order to achieve the objectives of the study. The researchers used the analytical descriptive method and the questionnaire was used as the main tool for data collection. The results of the study show that the level of the influence of the organizational structure on the organizational commitment achieved an arithmetic mean (4.12), and a standard deviation (629.). This is a high percentage, while the level of influence of the organizational culture of the university staff on the organizational commitment achieved an arithmetical mean (3.99), and a standard deviation (660.). This is a high percentage, with statistically significant differences in the level of influence of the organizational culture on the organizational commitment of university employees this according to the gender variable in favor of males over females. Based on these results, the study recommended the need for further research and studies on the impact of the internal environment and its dimensions in achieving the organizational commitment to come out with more recommendations that will enhance the role of higher education institutions in achieving their duties and objectives.